2016
DOI: 10.30958/ajh.3-3-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the PLISSIT Model in Solving Postpartum Sexual Problems Experienced by Women

Abstract: The aim of this study was to evaluate the effectiveness of the PLISSIT [Permission (P), Limited Information (LI), Specific Suggestions (SS) and Intensive Therapy (IT)] model in dealing with postpartum sexual problems. This was a quasi-experimental study with a pretest, a post-test and a control group made with 123 women (intervention=61; control=62). Before the application of the PLISSIT Model intervention plan, 77.0% of the women in the intervention group and 71.0% of the women in the control group had statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…More than half of the studied women were related to nuclear families. This similar to the findings of [36] reported that the majority of subjects were living in nuclear families.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More than half of the studied women were related to nuclear families. This similar to the findings of [36] reported that the majority of subjects were living in nuclear families.…”
Section: Discussionsupporting
confidence: 91%
“…Minority of studied women and their husbands had health problems while the majority of women sleeping with their children, similar to a study about " Sexual problems in women during the first postpartum year and related conditions" conducted by [2] they revealed that 10.4% of the studied women and 5.7% spouses had health problems while 71.3% of them reported that they were sleeping in the same room with their babies.The current study findings illustrated that, there were highly statistical significant differences between women regarding mean scores of Arizona Sexual Experiences Scale before and after the PLISSIT Model sexual counseling program. This finding approved by [36], who stated that, before the application of the PLISSIT Model intervention, most of women were facing sexual problems according to the Arizona Sexual Experiences Scale. However, after the application of the PLISSIT Model, a lesser proportion of the women were facing sexual problems.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the post-childbearing period, most women try to return to their sexual life within 8 to 12 weeks after childbirth. However, it may take up to 1 year to resume sexual relationships with the same quality of before pregnancy [9]. Psychotherapy and pharmacotherapy are two main methods for treating female sexual dysfunction (FSD) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that sexual dysfunction is prevalent in the postpartum period, especially during the rst 3 months after delivery; 41% -83% of women experience at least one type of sexual dysfunction during the rst three months after childbirth (4,5). Although most women resume their sexual activities within the rst three months after having given birth, 83% of these women experience sexual problems and while their sexual problems drop to 64% in the rst sixth month, 38% of them are never able to experience the same quality of sexual life compared to before pregnancy (6). Previous studies recognized some factors associated with sexual dysfunction such as primiparity, exclusive breastfeeding, age, type of delivery, education, time since delivery, mode of birth, family income, and partnership problems (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%